A Survey on Fault Tolerance in Wireless Sensor Networks - Alrajei, Nancy; Fu, Huirong (American Society for Engineering Education, 2014)
Wireless Sensor Networks (WSN) are useful for monitoring of physical conditions and passing the data gathered to the required location. They are like any other system prone to failure due to limitation of resources. In this paper we address fault tolerance concept in general, give analysis to the definition of fault tolerance and terms related to it based on the system requirements. We explored redundancy and touched upon fault tolerance in Wireless Sensor Networks. Topics covered include redundancy in hardware, N- Modules Redundancy (NMR), and software including N-version programming and check pointing. We also cover fault tolerance in Wireless sensor networks including connectivity and coverage and multipath.
All human-made systems are fault-prone. With each technology emerges, we cannot predict if it will continue to work happily ever after or not.
Keywords: fault tolerance; fault prevention; redundancy; dependability; connectivity; coverage; multiple path